2022
DOI: 10.3390/sym14050943
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning for Rupture Risk Prediction of Intracranial Aneurysms: Challenging the PHASES Score in Geographically Constrained Areas

Abstract: Intracranial aneurysms represent a potentially life-threatening condition and occur in 3–5% of the population. They are increasingly diagnosed due to the broad application of cranial magnetic resonance imaging and computed tomography in the context of headaches, vertigo, and other unspecific symptoms. For each affected individual, it is utterly important to estimate the rupture risk of the respective aneurysm. However, clinically applied decision tools, such as the PHASES score, remain insufficient. Therefore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…Tang et al ( 18 ) developed a predictive model by studying intracranial mirror aneurysms and concluded that neck width, bleb formation, and size ratio were independent risk factors for aneurysm rupture, which yielded good results in a validation cohort. Walther et al ( 19 ) demonstrated that the machine learning approach is better than the PHASES score for rupture prediction of UIAs, particularly for patients in geographically constrained areas.…”
Section: Discussionmentioning
confidence: 99%
“…Tang et al ( 18 ) developed a predictive model by studying intracranial mirror aneurysms and concluded that neck width, bleb formation, and size ratio were independent risk factors for aneurysm rupture, which yielded good results in a validation cohort. Walther et al ( 19 ) demonstrated that the machine learning approach is better than the PHASES score for rupture prediction of UIAs, particularly for patients in geographically constrained areas.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue, a brand-new approach by a research group from the University of Leipzig uses artificial intelligence for aneurysm rupture risk assessment. A large (N = 446), balanced database from the authors' medical center is engaged in a retrospective study using a gradient-boosting machine from the scikit-learn library and the R-package for statistical computing [4]. Challenging results came from this research, calling for optimistic yet cautious interpretations.…”
Section: Bodymentioning
confidence: 99%
“…Aneurysm size and other comorbidities such as diabetes and hypertension, classically considered triggers for aneurysm rupture, were less critical. The machine learning approach [4] improved the aneurysm rupture prediction performance [16]. However, the receiver operating curve of classical scoring ("PHASES score") in the databases of Bijlenga et al, and Walther et al, is not similar, which might harbor a confounding factor.…”
Section: Bodymentioning
confidence: 99%
See 1 more Smart Citation